Empowerment “Cassava Chips” Group Based on Pre Prosperity Family in Menteng and Neglasari Village - . Burhanuddin; Tintin Sarianti; . Mintarti (Institut Pertanian Bogor, 2018)
Empowerment cassava chips group based on pre prosperity family in Menteng Village, Bogor City and Neglasari Village, Bogor District purposed for reducing sum of poor family at two location. The special purpose is increasing income for poor families as the programme participants. The boundaries of poor family for the activity are pre prosperity family that have characteristic they could not eat twice a day, not have enough cloth for any activities, house condition not feasible, they could not access the health facilities and school because lack of budget. Steps of methode for building the new entrepreneur group based on pre prosperity family are 1) Selection and target approach; 2) Form the UMKM Miraos as “builder”; 3) Pre test; 4) Business motivation training, processing cassava chip training, marketing, and management business training; 5) Field study; 6) Introducing of suporting equipment for business; 7) Coaching and partner expansion; and 8) Post test. The result of empowerment activities resulted two groups small enterprises of cassava chips at both location. The two groups have earned additional income about IDR 60.000–150.000 per member in one cycle production after join the program. They also achieve increasing of knowledge and motivation about cassava chips business.